Customer Interest in Using BSI e-Banking During the Covid-19 Pandemic: Relationships Between Benefit Perceptions, Trust, and Personal Attitude - Dewi, Siska; Hidayati, Athi'; Qomar, Moh Nurul (MALIA: Journal of Islamic Banking and Finance, 2022)
The phenomenon of the COVID-19 pandemic motivates this research, as it shifts people's lifestyles to a cashless society, resulting in an increase in e-banking growth during the pandemic period. The goal of this study is to see how perceived benefits, trust, and personal attitude affect interest in using BSI e-banking during the COVID-19 pandemic. This research method employs quantitative methods as well as sampling techniques with secondary objectives. This study was conducted in Kudus city, with respondents being BSI e-banking users. The data was gathered through the use of a questionnaire, which was distributed to 96 respondents. The findings revealed that during the COVID-19 pandemic, the benefit perceptions, trust, and personal attitude all had a positive and significant effect on interest in using e-banking. Because the COVID-19 pandemic has not yet ended, e-banking will continue in the future. So, service providers like BSI must increase these deciding factors to encourage long-term use. They can do this by making users happier with the benefits of the product and by showing high integrity to build trust. This will give users a good attitude that makes them want to keep using the product